Central African Economic and Monetary Community : Recent Developments and Regional Policy Issues. (IMF Staff Country Reports; Country Report, 2005)
This paper on recent developments and regional policy issues in the Central African Economic and Monetary Community (CEMAC) discusses the recent development and trends in economic integration. Trade restrictions and an uneven application of CEMAC rules constrain external and intraregional trade. CEMAC officials agreed that further trade growth will require renewed commitment to abide by common trading rules. CEMAC faces important structural challenges, such as the weak financial sectors in several member countries and the need to increase competitiveness in the non-oil segments of the region's economies.